Relationship between word reading skills and reading comprehension - Vieiro, Pilar; Amboage, Isabel (Revista de Investigación en Logopedia, 2016)
Reading is an instrumental learning to be taught a specific method, in this sense, it is important to understand the interrelationship between the different threads involved. In this context, the general objective of this study is to examine whether an association or dissociation between the skills of word reading and comprehension processes in students of 2nd cycle of Primary Education and from there analyze the educational implications of the results obtained there. The initial sample consisted of 39 children from 4th Primary Education. The relevant analysis results showed that more important things: a) The level of reading comprehension measured by drawing inferences (activation of textual information) seems to appear independent of other variables (related to the lexicon and vocabulary); b) a low level lexicon or vocabulary (as measured by standardized tests) should not imply a low level of inferences; c) the working memory significantly affects the effectiveness of phonological awareness tasks and lexical access in general; d) there is a positive significant relationship between phonological awareness and visual access to the lexicon.